Policy on The Certainty of Legal Protection for Child Victims of Cyberbullying in Surakarta - Illyas Anshori; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2025)
This research aims to determine the policy of ensuring legal protection for child victims of cyberbullying in Surakarta. Technological developments and the presence of the internet have had a big impact on various aspects of life. One of the impacts is the emergence of the phenomenon of cyberbullying, which refers to bullying through digital media such as social media, messaging applications and other platforms. This research uses a normative juridical approach method which uses secondary data sources which contain several regulations such as the Criminal Code, Information and Electronic Transactions Law, Child Protection Law, Surakarta Regional Regulations and Ministry of Education Regulations. To collect data in this research, the author used literature study techniques which were supported by data from cyberbullying case reports in Surakarta as well as the results of interviews with the KAKAK Foundation, then analyzed qualitatively. Based on the results and discussion in this research, it is known that preventive legal protection in Surakarta has several laws and regulations which can be used as the basis for legal and repressive protection, such as efforts to handle cases through mediation, collaboration, provision of service posts, and education.